Selective Blockade of Interferon-α and -β Reveals Their Non-Redundant Functions in a Mouse Model of West Nile Virus Infection - Sheehan, Kathleen C. F.; Lazear, Helen M.; Diamond, Michael S.; Schreiber, Robert D. (PLOS ONE, 2015)
Although type I interferons (IFNs) were first described almost 60 years ago, the ability to monitor and modulate the functional activities of the individual IFN subtypes that comprise this family has been hindered by a lack of reagents. The major type I IFNs, IFN-β and the multiple subtypes of IFN-α, are expressed widely and induce their effects on cells by interacting with a shared heterodimeric receptor (IFNAR). In the mouse, the physiologic actions of IFN-α and IFN-β have been defined using polyclonal anti-type I IFN sera, by targeting IFNAR using monoclonal antibodies or knockout mice, or using Ifnb-/- mice. However, the corresponding analysis of IFN-α has been difficult because of its polygenic nature. Herein, we describe two monoclonal antibodies (mAbs) that differentially neutralize murine IFN-β or multiple subtypes of murine IFN-α. Using these mAbs, we distinguish specific contributions of IFN-β versus IFN-α in restricting viral pathogenesis and identify IFN-α as the key mediator of the antiviral response in mice infected with West Nile virus. This study thus suggests the utility of these new reagents in dissecting the antiviral and immunomodulatory roles of IFN-β versus IFN-α in murine models of infection, immunity, and autoimmunity.